THE VIEW UI VOCATIONAL STUDENTS IN MANAGING PERSONAL RECORDS TO GET DIPLOMA SUPPLEMENT - Safitri, Dyah; Wahyuni, Titis (Journal of Documentation and Information Science, 2017)
Personal file record is very important for the students to support the activities. If the personal records can be organized properly, they can fill Sipresma (Sistem Informasi Prestasi Mahasiswa) or student achievement information system easily. The rules also require that students can manage a personal record in the form of a charter, certificate or other reference letter to get diploma supplement or Surat Keterangan Pendamping Ijazah (SKPI). In this study objectives are to determine the management of personal records related to student achievement information system (Sipresma) UI. This research method uses quantitative methods involving 358 respondents of the Vocational Education Program University of Indonesia students. The results obtained showed that the majority of students agreed that the personal file management still not maximal. The conclusion from this study also shows that the students are very aware of the certificate or reference of activity should be stored in a special storage area that's personal record can be well ordered